DOA Estimation Method Based On Improved Variable-Step-Size LMS Algorithm - Qin, Yongfeng; Li, Simin; Tang, Zhiling (2021 International Symposium on Computer Technology and Information Science (ISCTIS), 2021)
As an important branch of array signal processing, the beamforming algorithm can form gain in the direction of the desired signal and null in the direction of the interference signal, which can effectively suppress the interference of multipath signals. To address the problem that the classical spatial spectrum estimation algorithm does not have high resolution for the estimation of coherent sources, a DOA estimation method based on the Witch function and normalization of variable-step-size LMS algorithm is proposed in this paper. By defining the reciprocal of the array pattern as the spatial spectrum, the proposed method regards the DOA estimation as a peak search. The simulation results show that the proposed method can effectively suppress the interference of multipath signals. And it has similar performance with the classical spatial spectrum estimation method. Compared with other beamforming methods, the proposed method has convergence speed and better stead-state performance.